Zdroij . Source - Mareček, Martin (Slajer, Vratislav ; Fabianova, Barbora, 2005)
Duration: 01:15:00 Baku in Azerbaijan, with some of the richest deposits of oil in the world, is becoming a focus for foreign investors eager to take advantage of the country’s natural resources. Source traces the 'Great Oil Road' from European highways to this surreal and sinister landscape, where cows graze on polluted land and children play in toxic gunge. With three quarters of the population living under the poverty line, the country’s post-Soviet government is promising that oil will turn Azerbaijan into a prosperous and flourishing ‘New Kuwait’. But between big oil companies like British Petroleum and the corrupt government lining their pockets, what does this mean for the ordinary people of Azerbaijan? Is this “liquid gold” more of a curse or a blessing for the country?